Research on the Theory and Practice of the Fair Competition Review System in China - Peng, Yanling; Ying, Pinguang (Advances in Social Sciences Research Journal, 2021)
On June 1, 2016, the State Council of the People’s Republic of China released its Opinions on Establishing a Fair Competition Review System in the Development of the Market System. It shows the determination of Chinese center government that firmly protect the Market System. Actually, the Chinese government is always making the effort to decrease the inappropriate intervention to Market System which from the public rights. Up to now, remarkable results have been achieved. And the stable and rapid growth of China’s economy is the best proof. The release of the document about Fair Competition Review is conducive to consolidating the previous achievements of the Chinese government. The purpose of this paper is to introduce the content of this system and put forward some suggestions based on the actual situation in China.